(untitled) (Heritage, 2022)
Court balls, organized in Serbia in the 19th century at princely and royal courts, modeled on European ones, were labeled for a certain class of society, which gave these social events a festive note and a certain reputation. By coming to the ballс, people had already integrated into the highest cultural ranks and by adopting new elements of behavior they significantly differed from other categories of residents. Therefore, balls of the highest rank were important social events because participation in them proved membership in that circle and superiority over others in every respect. However, although the European cultural pattern dominated the balls, elements of traditional, national culture also appeared in it, in accordance with the general circumstances.